Imaging markers of intracerebral hemorrhage expansion in patients with unclear symptom onset. Issue 9 (October 2022) - Morotti, Andrea; Boulouis, Gregoire; Charidimou, Andreas; Poli, Loris; Costa, Paolo; Giuli, Valeria De; Leuci, Eleonora; Mazzacane, Federico; Busto, Giorgio; Arba, Francesco; Brancaleoni, Laura; Giacomozzi, Sebastiano; et al.
Background: Hematoma expansion (HE) is common and associated with poor outcome in intracerebral hemorrhage (ICH) with unclear symptom onset (USO). Aims: We tested the association between non-contrast computed tomography (NCCT) markers and HE in this population. Methods: Retrospective analysis of patients with primary spontaneous ICH admitted at five centers in the United States and Italy. Baseline NCCT was analyzed for presence of the following markers: intrahematoma hypodensities, heterogeneous density, blend sign, and irregular shape. Variables associated with HE (hematoma growth > 6 mL and/or > 33% from baseline to follow-up imaging) were explored with multivariable logistic regression. Results: Of 2074 patients screened, we included 646 subjects (median age = 75, 53.9% males), of whom 178 (27.6%) had HE. Hypodensities (odds ratio (OR) = 2.67, 95% confidence interval (CI) = 1.79–3.98), heterogeneous density (OR = 2.16, 95% CI = 1.46–3.21), blend sign (OR = 2.28, 95% CI = 1.38–3.75) and irregular shape (OR = 1.82, 95% CI = 1.21–2.75) were independently associated with a higher risk of HE, after adjustment for confounders (ICH volume, anticoagulation, and time from last seen well (LSW) to NCCT). Hypodensities had the highest sensitivity for HE (0.69), whereas blend sign was the most specific marker (0.90). All NCCT markers were more frequent in early presenters (time from LSW to NCCT ⩽ 6 h, n  = 189, 29.3%), and more sensitive in this population as well (hypodensities had 0.77 sensitivity). Conclusion: NCCT markers are associated with HE in ICH with USO. These findings require prospective replication and suggest that NCCT features may help the stratification of HE in future studies on USO patients.